Cop Town [large type] : a novel - Slaughter, Karin, 1971- (Center Point Large Print, 2014)
"In 1974, the Atlanta Police Department is investigating a serial cop killer hardly welcomes women, so they partner Kate and Maggie to isolate them from the action. But the move will backfire, putting them right at the heart of it"--